Culture-based characterization of gut microbiota in inflammatory bowel disease - Hyunjoon Park; Soyoung Yeo; Soyoung Yeo; Taekyu Lee; Yumin Han; Chang Beom Ryu; Chul Sung Huh; Chul Sung Huh (Frontiers in Microbiology, 2025)
Inflammatory bowel disease (IBD) is characterized by disruptions in the gut microbiome. While most studies on gut dysbiosis in IBD rely on sequencing-based methods, we employed a streamlined culturomics approach to obtain a more comprehensive understanding of gut microbiota imbalance in patients with IBD that may not be captured by sequencing alone. A total of 367 bacteria were identified at the species level, including 211 species from ulcerative colitis patients, 164 species from Crohn’s disease (CD) patients, and 263 species from healthy individuals. Consistent with our 16S rRNA gene amplicon sequencing results, a significant decrease in microbial diversity and a severe imbalance, especially in CD patients, were also observed in the culture-based analysis. Our culturomics approach provided additional insights, highlighting dysbiosis in unique anaerobic and Gram-negative species in CD patients. Moreover, species-level findings for Bifidobacterium and Enterobacterales emphasized specific species expansions in IBD patients. Notably, Mediterraneibacter gnavus, Thomasclavelia ramosa, Parabacteroides merdae, and Collinsella aerofaciens are of particular clinical interest due to their correlation with inflammatory biomarkers. This comprehensive analysis underscores the value of integrating a culture-based approach with a genome-based approach to provide complementary insights and therapeutic targets in IBD.